(untitled) (Sociologisk Forskning, 2019)
Contemporary welfare policies often frame the unemployed as ”job seekers”, a position which demands that the individual engages in active job seeking, continuous self-work and various employability-enhancing activities. This article examines how the unemployed, through digital job coaching webinars by Arbetsförmedlingen (the Swedish Public Employment Service), are positioned and steered as job seekers. By scrutinizing the advice in the material with the help of theories of ”immaterial labor” and ”biopolitics”, the article conceptualizes job seeking as a kind of labor which dissolves common distinctions between work, unemployment and leisure time. Three themes are analyzed: how job seekers are activated and responsibilized; how they are encouraged to engage in affective self-work; and how they are recommended to brand and market themselves as products. By approaching job seeking as immaterial labor, it is argued that we better can grasp the wider importance of reproductive activities during unemployment for generating value in post-Fordist economies.